Results of experimental modeling of stresses on fixators in metal osteosynthesis of transtrochanteric fractures - A.V. Kalashnikov; Y.K.M. Sabarna (Bolʹ, Sustavy, Pozvonočnik)
Background. In the world’s developed countries, minimally invasive technologies for using the proximal femoral rod are widely implemented in treating fractures of the proximal femur. However, we did not find literature data on the stresses on the blocked intramedullary rod depending on the type of fracture due to АО (Association of Osteosynthesis) and variants of its distal blocking. The study aimed to carry out biomechanical modeling of stresses on various metal fixators in osteosynthesis for transtrochanteric fractures of type A1. Materials and methods. We used a model of the femur, in which fixing elements were implanted. Two types of fixators were used to fix the fragments — the DHS (dynamic hip screw) plate (option 1) and the proximal femoral nail (PFN, option 2) rod, which provide optimal biomechanical and biological conditions for fracture union. Calculations of stress-strain state by the finite element method were performed for the intact model with both types of fixators and then with fixators for transtrochanteric fractures type A1 and options for distal locking (without locking, 1 screw, 2 screws). It was determined that the minimum stress on the metal fasteners in their proximal parts was determined when using the DHS plate and the PFN rod in the version without the use of screws for distal locking. Results. Our results were significantly (p ≤ 0.05) different from the data when using a PFN rod with distal locking with 1 or 2 screws. There was no stress on the distal part of the metal retainers when the PFN rod was applied in the variant without the use of screws for distal locking. In contrast, the stress when the DHS plate was applied increased to maximum values of 57.18 MPa. It was determined that maximum but adequate micromobility was observed when using the PFN rod model in the version without the use of screws for distal locking. These micromovements will contribute to the improvement of reparative osteogenesis of patients with type A1 transtrochanteric fractures. Fixation that is too strong when using a DHS plate (1.95 mm) can lead to impaired reparative osteogenesis. Conclusions. The research will make it possible to determine a differentiated approach to treating patients with transtrochanteric fractures of the femur. It will improve the effectiveness of providing medical care to this severe category of patients.